Decidual stromal cells drive CD16+ macrophages towards an immunoregulatory phenotype via extracellular matrix-adhesion molecule interaction during early pregnancy - Yang, Hui-Li; Shi, Jia-Wei; Lai, Zhen-Zhen; Li, Xin; Gu, Chun-Jie; Zheng, Zi-Meng; Zhao, Hong-Bo; Ye, Jiang-Feng; Wang, Li; Peng, Ting; Li, Ming-Qing (Frontiers in Immunology, 2026)
IntroductionDramatic alterations of the extracellular matrix (ECM), which can regulate cell behavior by binding to adhesion molecules and are intrinsically linked to immune regulation, occur in decidualization during early pregnancy. Decidual macrophages (dMφ) are a group of tissue-resident cells with an affinity for adhesion. An interactive dialogue occurs between decidual stromal cells (DSCs) and dMφ, however it remains unclear whether this process is associated with ECM-adhesion molecules. This study was conducted to investigate the cross-talk of DSC and CD16+ dMφ via extracellular matrix-adhesion molecule interaction in early pregnancy.MethodsSingle-cell sequencing data from endometrial and decidual tissues were analyzed to elucidate the interactions between DSCs and dMφ. We assessed the levels of ECM components in the decidua at the tissue or cellular levels, and examined the expression of adhesion molecules and polarization molecules in CD16+ or CD16- dMφ. Then we validated DSC-CD16+ Mφ interactions using the co-culture system. Finally, we evaluated the levels of ECM components in decidua and the expression of molecules in dMφ in patients with recurrent miscarriage (RM).ResultsDSCs communicated with dMφ via ECM-adhesion molecules. Collagen IV, osteopontin (OPN) and hyaluronic acid (HA) derived from DSCs promoted the development of CD16+ dMφ and their differentiation toward an immunomodulatory phenotype via their receptors, which is beneficial for maintaining immune tolerance. In patients with RM, decidua exhibits weakened ECM-CD16+ dMφ regulatory link, which may be associated with the underlying pathogenesis.DiscussionThis study confirms that DSC can regulate the immune status of CD16+ dMφ through the ECM-adhesion molecule axis, further elucidating the regulatory mechanisms of Mφ during decidualization. Exploration of therapeutic strategies based on ECM-receptor-mediated stroma-immune interactions holds promise as novel treatment approaches for miscarriage.